Dietary Practices and Nutritional Status of Adolescent Girls in Ko Senior High Boarding School in Theupper West Region - Aganah, C.A. (University of Ghana, 2014)
Background: Adolescence is an important growth and development life stage which has implications for future nutritional status and food consumption habits. School meals may offer an opportunity to enhance dietary intakes and nutritional status of adolescent girls in boarding school settings. However, there is limited information on the nutritional quality of school meals, dietary habits and nutritional status of adolescent girls in senior high boarding schools in Ghana. Objective: The aim of the study was to assess the dietary practices and nutritional status of adolescent girls in Ko Senior High Boarding School. Methodology: A cross-sectional survey of 180 adolescent school girls was used in this study. Semi-structured questionnaire was used to solicit information on the girls‟ socio-demographic characteristics and dietary practices. The 24-hour recall method was used to obtain information on dietary intakes on 2 non-consecutive days. Additionally the weighed food method was used to ascertain weights of foods consumed daily from the school dining hall by a random sample of the girl over a two weeks period. The girls‟ height and weight measurements were also taken. Descriptive statistics, bivariate and regression analysis were used to summarize the data and to assess for factors associated with the girls‟ dietary practices and nutritional status. Results: Meal skipping, particularly breakfast was observed as the main unhealthy eating habit among adolescent girls in Ko Senior High Boarding School. Niacin, folate, riboflavin, calcium, vitamin B12 and vitamin D intakes were found to be below the recommended dietary reference intakes (EAR). The prevalence of stunting, thinness or low BMI for age and overweight as observed among the girls were 2.2%, 1.2% and 16.1% respectively. Conclusion: The Mean % contribution of school meals and other food sources to the total daily nutrient intakes of adolescent girls in Ko Senior High Boarding School was reported in this study to be 56.2 and 43.8 respectively. Following this, the quantity and quality of school meals served to the girls needs to be reviewed by school authorities to increase its contribution to daily nutrient intakes.
Thesis(MPHIL)-University of Ghana, 2014
Keywords: Dietary Practices; Nutritional Status; Adolescent Girls; Ko Senior High Boarding School